Applying an Arts-Integrated Approach in English Language Material Development for PGSD Students in Distance Education - SUPARTI, SUPARTI; Yusak, Suharno (LPPM Universitas Terbuka, 2025)
The development of contextualized English teaching materials is very important for PGSD students, especially in the distance learning system at the Open University. This research aims to apply an arts integrated approach to the development of English language materials to improve students' learning engagement and understanding. This approach incorporates elements of visual art, creative expression and aesthetic values into language learning content. The method used was R&D with the ADDIE model. Data were obtained from observation, questionnaires, and interviews, then analysed descriptively qualitatively. The results showed that more than 85% of students felt the material was easier to understand because of the visual elements. Students also became more active, completed tasks more quickly, and retained vocabulary for longer periods. Final products such as visual journals, picture vocabulary cards, and mini storybooks reflected improved language comprehension as well as pedagogical creativity. These findings support the arts-integrated approach as an effective learning strategy in developing English teaching materials within a distance education context.